FLATFOOT CORRECTION IN PRIMARY SCHOOL AGED CHILDREN BY METHODS OF PHYSICAL THERAPY - Листау, Карина (SWorldJournal, 2021)
Foot deformity occupies one of the important places among diseases of the musculoskeletal system. Flatfoot begins in childhood, progresses in adolescence, and eventually becomes a deformity of the foot in adulthood. Today, flatfoot is one of the most com